Phenolic Imidazole Derivatives with Dual Antioxidant/Antifungal Activity: Synthesis and Structure-Activity Relationship - Bettencourt, Ana P.; Castro, Marián; Silva, João P.; Fernandes, Francisco; Coutinho, Olga P.; Sousa, Maria J.; Proença, Maria F.; Areias, Filipe M. (Medicinal Chemistry, 2019)
Background: Previous publications show that the addition of a phenolic antioxidant to an antifungal agent, considerably enhances the antifungal activity. Objective: Synthesis of novel compounds combining phenolic units with linear or cyclic nitrogencontaining organic molecules with antioxidant/antifungal activity using methodologies previously developed in the group. Methods: Several N- [1,2-dicyano-2- (arylidenamino) vinyl]-O-alkylformamidoximes 3 were synthesized and cyclized to 4,5-dicyano-N- (N´-alcoxyformimidoyl)-2-arylimidazoles 4 upon reflux in DMF, in the presence of manganese dioxide or to 6-cyano-8-arylpurines 5 when the reagent was refluxed in acetonitrile with an excess of triethylamine. These compounds were tested for their antioxidant activity by cyclic voltammetry, DPPH radical (DPPH•) assay and deoxyribose degradation assay. The minimum inhibitory concentration (MIC) of all compounds was evaluated against two yeast species, Saccharomyces cerevisiae and Candida albicans, and against bacteria Bacillus subtilis (Gram-positive) and Escherichia coli (Gram negative). Their cytotoxicity was evaluated in fibroblasts. Results: Among the synthetised compounds, five presented higher antioxidant activity than reference antioxidant Trolox and from these compounds, four presented antifungal activity without toxic effects in fibroblasts and bacteria. Conclusion: Four novel compounds presented dual antioxidant/antifungal activity at concentrations that are not toxic to bacteria and fibroblasts. The active molecules can be used as an inspiration for further studies in this area.
Keywords: cancer